Synthesis of thermo-sensitive polymers with super narrow molecular weight distributions: PET-RAFT polymerization of N-isopropyl acrylamide mediated by cross-linked zinc porphyrins with high active site loadings. Issue 15 (23rd March 2021) - Li, Fanfan; Yu, Yi; Lv, Hanyu; Cai, Guiting; Zhang, Yanwu
Abstract : To overcome the aggregation of porphyrins and realize heterogeneous photo-catalysis with high active site loadings, twisted ZnTHP–Me2 Si and layered ZnTHP–Ph2 Si are prepared through cross-linking zinc porphyrins by different chlorosilanes. Abstract : To overcome the aggregation of porphyrins and realize heterogeneous catalysis with high active site loadings, twisted ZnTHP–Me2 Si and layered ZnTHP–Ph2 Si are synthesized by cross-linking 5, 10, 15, 20-tetrakis(4-hydroxyphenyl)porphyrin zinc (ZnTHP) respectively with dichlorodimethylsilane and dichlorodiphenylsilane. The microstructures of both ZnTHP–Me2 Si and ZnTHP–Ph2 Si are investigated, and their active site loadings were found to be greater than 0.8 mmol ZnTHP per g ZnTHP-Me2 Si or per g ZnTHP-Ph2 Si. Furthermore they act as photocatalysts in the photoinduced electron transfer reversible addition–fragmentation chain transfer (PET-RAFT) polymerization of N -isopropyl acrylamide (NIPAm) under green light. The results indicate that both of them show more effective photocatalytic performance than ZnTHP and demonstrate the attractive features of living polymerization. Moreover, twisted ZnTHP–Me2 Si with a larger surface area and pore distribution can accelerate the polymerization of NIPAm more effectively. According to the MALDI-TOF analysis, the dispersity of the as-synthesized poly( N -isopropyl acrylamide) (PNIPAm) catalyzed by ZnTHP–Me2 Si is less than 1.100 and the minimum value can reach 1.049. The excellent recyclability of ZnTHP–Me2 Si is also confirmed by repeated PET-RAFT polymerization cycles, albeit with a slight reduction of the catalyst activity. Therefore PET-RAFT polymerization mediated by cross-linked ZnTHP is a potential method to synthesize a thermo-sensitive polymer with a super narrow molecular weight distribution.